Santri Management Pondok Pesantren Salafiah - Kemal, Isthifa; Hasibuan, Rossy Anggelia; Setyanto, Eddy (Seminar Nasional Teknologi Edukasi Sosial dan Humaniora, 2021)
This study is a case study about the management of santri in Pondok Pesantren Salafiah Al-Wathoniyah 43 Jakarta. The methodology used in this study was qualitative with a case study intrinsic design. The data were collected by using interviews, participative observations and documentations. As a result, the study foud that the modern management of santri in Pondok Pesantren Al-Wathoniyah 43 Jakarta ran efectively in aspects of santri managements as well as planning and extracuriculler activities.